Revitalisasi Spirit Pemikiran Etika Gus Dur - Khasanah, Faizatun (Universitas Islam Negeri Raden Intan Lampung, 2019)
In this Modern era, human being identic with positivistic and materialistic thinking. In this step human out of religious and philosophic thinking. That gives impact to morality that lose from believe in God. This is urgency of this research at modern global era. Writer use philosophical approach and critical method. The result of this research is characteristic of Gus Dur ethic it’s religious-rational. The foundation of Gus Dur ethic is religious teaching, God gives human some of excess that are reason, moral and feel. From that, human have to responsibility to keep universe especially to human being, not to self-interest. Gus Dur ethic that based on religious and ratioanl approach is appropriate in this modern era, especially at Indonesian state, because Gus Dur is the figure that rise up Indonesian Islam (Islam Nusantara)